2001
DOI: 10.1111/j.1151-2916.2001.tb00913.x
|View full text |Cite
|
Sign up to set email alerts
|

Wet Erosive Wear of Alumina Densified with Magnesium Silicate Additions

Abstract: A study was made of the wet erosive wear of polycrystalline alumina of mean grain size >1 m, containing up to 10 wt% of magnesium silicate sintering aid. For pure polycrystalline alumina, the dominant wear mechanism was grain-boundary microfracture, leading to partial or complete grain removal. In the case of the liquid-phase-sintered materials, wear rates could be as low as 25% of those of pure alumina of the same mean grain size, and the main material removal mechanism was transgranular fracture combined wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Previous work 5,7,8 has shown that ceramic materials with smaller median grain size show lower wear rates. This is summarized in the graph shown in Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous work 5,7,8 has shown that ceramic materials with smaller median grain size show lower wear rates. This is summarized in the graph shown in Fig.…”
Section: Discussionmentioning
confidence: 98%
“…A similar behaviour has been found in previous studies where chemical etching was employed. 5 It is possible that this behaviour can be linked to the chemistry of the intergranular and secondary crystalline phases and also to the thermal shock applied during etching on the heavily defective microstructure of the CSp specimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because they as the silicate had a marked grain-boundarystrengthening action and as grain-boundary phase could clearly suppressed grain-growth when the grain zone were completely covered by the continuous silicate phase, even at extremely low concentrations. 30 The calcium silicate-densified alumina examined earlier showed the amorphous silicate films at all the two-grain boundaries, of order of 2 nm thickness. 31 The SEM examinations ( Fig.…”
Section: Microstructure and Densification Characterizationmentioning
confidence: 98%
“…Toughening of A1 2 0 3 is worked upon by using secondary phases as additives, consolidating nanocrystalline A1 2 0 3 powder particles via pressing and sintering, and reinforcing with particulates, fibers or whiskers [35,[121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136]. Following example elicit specific examples of toughened A1 2 0 3 ceramic.…”
Section: Toughening Of Aluminum Oxidementioning
confidence: 99%